Fumarate Analogs Act as Allosteric Inhibitors of the Human Mitochondrial NAD(P)+-Dependent Malic Enzyme - Hsieh, Ju-Yi; Liu, Jyung-Hurng; Yang, Pai-Chun; Lin, Chi-Li; Liu, Guang-Yaw; Hung, Hui-Chih (PLOS ONE, 2014)
Human mitochondrial NAD(P)+-dependent malic enzyme (m-NAD(P)-ME) is allosterically activated by the four-carbon trans dicarboxylic acid, fumarate. Previous studies have suggested that the dicarboxylic acid in a trans conformation around the carbon-carbon double bond is required for the allosteric activation of the enzyme. In this paper, the allosteric effects of fumarate analogs on m-NAD(P)-ME are investigated. Two fumarate-insensitive mutants, m-NAD(P)-ME_R67A/R91A and m-NAD(P)-ME_K57S/E59N/K73E/D102S, as well as c-NADP-ME, were used as the negative controls. Among these analogs, mesaconate, trans-aconitate, monomethyl fumarate and monoethyl fumarate were allosteric activators of the enzyme, while oxaloacetate, diethyl oxalacetate, and dimethyl fumarate were found to be allosteric inhibitors of human m-NAD(P)-ME. The IC50 value for diethyl oxalacetate was approximately 2.5 mM. This paper suggests that the allosteric inhibitors may impede the conformational change from open form to closed form and therefore inhibit m-NAD(P)-ME enzyme activity.